Potential of Vegetable Commodities on Sustainable Agriculture Perspective: Evidence from Kolaka Regency, Indonesia - Amin, Muhtar; Kasmin, Muh. Obi; Nurhapsa, Nurhapsa; Suparman, Suparman; Irwansyah, Irwansyah (Universitas Panji Sakti, 2025)
. Regional growth will be optimally driven by commodity development that establishes itself as a base industry and has the potential to grow greatly. One of the most effective ways to boost economic development in a region is through commodity development, and it has good sustainability potential. This study aims to analyse basic vegetable commodities and examine the sustainability of these basic commodities in Kolaka Regency. The data used in this research are time series data on vegetable production for 2019-2023, which were analysed using the location quotient and dynamic location quotient methods. The research results show that the vegetable products that have good development prospects based on LQ and DLQ values greater than 1 are cayenne pepper, chayote and eggplant. The results of this research can be used as reference material for formulating policies in the context of vegetable product development in Kolaka Regency.